The Self-Determination Inventory: Student Report American Sign Language Translation. (6th July 2022) - Garberoglio, Carrie Lou; Gerasimova, Daria; Shogren, Karrie A; Palmer, Jeffrey Levi; Johnson, Paige M; Ryan, Claire; Pace, Jesse R; Hicks, Tyler; Millen, Kaitlyn; Higgins, Jennifer; Cawthon, Stephanie W
Abstract: Research literature and community narratives both emphasize the importance of self-determination in the lives of deaf youth. This paper describes the development, initial validation, and potential applications of a translated measure of self-determination for deaf youth, the SDI:SR ASL Translation (SDI:SR ASL). A sample of 3, 309 young people who completed the SDI:SR, of whom 392 were deaf, was used in this validation study. Results provide preliminary support for the use of SDI:SR ASL with deaf youth. Findings also indicate that deaf youth who take the SDI:SR ASL score more similarly to youth without disabilities taking the SDI:SR than youth with disabilities. The SDI:SR ASL can be an important tool for researchers and practitioners to better understand self-determination among deaf youth and facilitate continued development of self-determination skills.